Monocyte/High-Density Lipoprotein Ratio Is an Indicator of Activity in Patients with Ulcerative Colitis - Yalçın, Mehmet Suat; Yalaki, Serkan; Ölmez, Şehmus; Taş, Adnan (Turkish Journal of Gastroenterology, 2022)
Background: In patients with ulcerative colitis, endoscopic and clinical indices are used to assess the disease activity. In addition, stud- ies have been carried out for easier and cheaper markers in recent years. For this purpose, we evaluated the monocyte/high-density lipoprotein ratio of the disease activity.Methods: According to clinical activity and partial Mayo scores, a total of 114 patients, 53 in the active ulcerative colitis group and 61 in the ulcerative colitis remission group were included in the study. Monocyte/high-density lipoprotein ratio, neutrophil/lymphocyte ratio, platelet/lymphocyte ratio, C-reactive protein, and erythrocyte sedimentation rate measurements of these 2 groups were recorded. Ulcerative colitis remission group and active ulcerative colitis group were compared in terms of activity.Results: The monocyte/high-density lipoprotein ratio value in the active ulcerative colitis group was significantly higher than that of the ulcerative colitis remission group (10.68 ± 3.39, 6.68 ± 1.39, P < .001, respectively). The monocyte/high-density lipoprotein ratio value for active ulcerative colitis at a cut-off value of 7.4 had 83% sensitivity and 81% specificity. In the active ulcerative colitis group, neutrophil/lymphocyte ratio, C-reactive protein, and erythrocyte sedimentation rate values were significantly higher than the ulcerative colitis remission group (P < .001, P < .001, P < .001, respectively).Conclusion: Monocyte/high-density lipoprotein ratio is an inexpensive and effective marker that can be used to determine the activity of ulcerative colitis.